Speech Control as A Preventive Strategy of Islamic Religious Education Teachers Against Verbal Bullying Behaviour - Muhammad Arbain; Mohammad Firman Maulana; Ramlan Padang (Fakultas Agama Islam, 2026)
This study aims to describe and analyze the strategies employed by Islamic Religious Education teachers in instilling the value of hifzh al-lisan (guarding one’s speech) as an effort to anticipate verbal bullying among students at SMP Pancasila Tanjung Beringin. The research was motivated by the tendency of students to normalize ridicule, inappropriate nicknames, and harsh language as part of everyday joking, which may negatively affect students’ character development and psychological well-being. This study employed a descriptive qualitative approach. Data were collected through participatory observation, in-depth interviews with key informants, including the principal, Islamic Religious Education teachers, subject teachers, homeroom teachers, and students, as well as documentation studies. Data were analyzed through data reduction, data display, and conclusion drawing. The findings revealed that verbal bullying commonly occurred in the form of mocking, labeling, and the use of offensive language among peers. Islamic Religious Education teachers addressed this issue through the integration of ethical communication values in classroom instruction, role modeling (uswatun hasanah), personal counseling, and collaborative supervision involving school stakeholders. Supporting factors included strong school leadership and teacher collaboration, while obstacles arose from peer culture, social media influences, and limited parental supervision. Overall, the strategy contributed positively to students’ communication ethics and awareness of respectful interaction.